Answer:
step 1: 100
step 2: is 100
Step 3: 5,600
Step-by-step explanation:
You get (2x+3)(4x^2-6x+9) when you factor 8x^3+27=0. You just divide by 3 to simplify it.
Answer:
6
Step-by-step explanation:
fred has 2 peanut butter and 3 jelly
type 1 peanut butter can go with all three types of jelly = 3 pb&js where ther is one constant peanutbutter and 3 different jellys
type 2 peanut butter can go with all three jellies = 3 pb&js where there is one constant peanutbutter and 3 different jellies
3+3=6
there are 6 peanut butter and jelly sandwhiches he could make.
you can also just multiply the numbers (2x3=6)